The Non-Ideality of the System Benzene + 1,2-Dichloroethane Adsorbed in Microporous Carbons at 293 K - F. Stoeckli; G. Couderc; A. Lavanchy; D. Wintgens; P. Girardin (Adsorption Science & Technology)
In the case of simple vapour mixtures adsorbed by active carbons, the activity coefficients seem to depend essentially on the composition of the adsorbed phase, rather than on the degree of micropore filling. Consequently, the liquid–solid adsorption equilibrium of benzene + 1,2-dichloroethane mixtures has been investigated at 293 K, using a typical active carbon and following earlier work for adsorption from the vapour phase. This system has the advantage that the mixture is ideal in the liquid state, which provides a convenient reference for the study of the adsorbed phase. The activity coefficients, as well as the excess enthalpy of immersion of the carbon into the liquid mixtures, provide information on the modifications in the adsorbed state with respect to the ideal mixture. It is also shown that the introduction of the activity coefficients derived from the solid–liquid equilibrium increases considerably the accuracy of the Myers–Prausnitz–Dubinin model for the adsorption of the vapour mixtures.